Analisis SWOT sebagai Strategi Pengembangan Bisnis Batubara pada PT. ELS - Wibowo, Kuncoro; Sarjana, Samuel Horas (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to analyze the strategic position of PT. ELS using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to formulate a sustainable business development strategy. Data were collected through company profile documents and secondary observations of operational and marketing activities. The analysis results indicate that the company’s main strengths lie in its extensive supplier and customer networks, product quality, and logistics efficiency. However, weaknesses include dependence on global coal price fluctuations and limited energy diversification. Market opportunities remain open, particularly in the Asian region, along with digital technology adoption, while major threats come from stricter environmental policies and the global transition toward clean energy. Based on these findings, short-term strategies include strengthening financial structures and operational efficiency, while long-term strategies involve diversification into alternative energy sources and enhancing regulatory compliance.